An update on the interaction between COVID-19, vaccines, and diabetic kidney disease - Yang, Yang; Zou, Shubiao; Xu, Gaosi (Frontiers in Immunology, 2022)
Up to now, coronavirus disease 2019 (COVID-19) is still affecting worldwide due to its highly infectious nature anrapid spread. Diabetic kidney disease (DKD) is an independent risk factor for severe COVID-19 outcomes, and they have a certain correlation in some aspects. Particularly, the activated renin–angiotensin–aldosterone system, chronic inflammation, endothelial dysfunction, and hypercoagulation state play an important role in the underlying mechanism linking COVID-19 to DKD. The dipeptidyl peptidase-4 inhibitor is considered a potential therapy for COVID-19 and has similarly shown organ protection in DKD. In addition, neuropilin-1 as an alternative pathway for angiotensin-converting enzyme 2 also contributes to severe acute respiratory syndrome coronavirus 2 entering the host cells, and its decreased expression can affect podocyte migration and adhesion. Here, we review the pathogenesis and current evidence of the interaction of DKD and COVID-19, as well as focus on elevated blood glucose following vaccination and its possible mechanism. Grasping the pathophysiology of DKD patients with COVID-19 is of great clinical significance for the formulation of therapeutic strategies.